TEST TAKERS’ ATTITUDES TO THE TEST CONTENT OF THE TWO LISTENING TESTS: IELTS AND TOEFL iBT - Hoa, Nguyen Thi Nhan (VNU Journal of Foreign Studies; Vol 34 No 4DO - 10.25073/2525-2445/vnufs.4280, 2018)
Ten aspects of test content in the two listening tests: IELTS and TOEFL iBT are investigated from the perspective of test-takers’ judgment. Main findings reveal that there are both similarities and differences in test takers’ attitudes to the two tests although the similarities outweigh the differences. The most obvious difference is that test takers have a more positive attitude to the IELTS listening test than to the TOEFL iBT listening test and test preparation has a strong effect to test takers’ attitude to the test. In addition, test takers’ positive attitudes to the test are strongly associated with better test performance. Substantial differences of test takers’ attitude to the two listening tests can be seen in their judgment of difficulty level, new words/technical terms and familiarity of topics. Test takers found the IELTS listening test less difficult, having fewer new words and technical terms, and containing more familiar topics than the TOEFL iBT listening test. They also find the test method of the IELTS is less challenging than that of the TOEFL iBT listening test although their choice of the test to take heavily depends on which test they are being prepared for.